2009
DOI: 10.1158/1078-0432.ccr-08-1171
|View full text |Cite
|
Sign up to set email alerts
|

Castration-Resistant Prostate Cancer: Locking Up the Molecular Escape Routes

Abstract: The understanding of the key role that androgens play on the normal and pathological physiology of the prostate guided the development of different therapies for the treatment of locally advanced or metastatic prostate cancer (PCa). These so-called androgen deprivation therapies include surgical or chemical castration, achieved by the administration of gonadotropin-releasing hormone analogs; inhibition of steroidogenic enzymes; and finally, blocking of the binding of androgens to their receptor (AR) by the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
161
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 53 publications
1
161
0
2
Order By: Relevance
“…Based on the central role of AR in castration resistance, novel AR pathway inhibitors could potentially provide important therapeutics for advanced prostate cancer (Attar et al 2009;Knudsen and Scher 2009). In this regard, a second-generation AR antagonist, MDV3100, which completely lacks agonist activity and binds AR with greater affinity than bicalutamide, has provided new insights into castration resistance, and has given promising results in mouse models and in a human phase 1-2 trial Scher et al 2010).…”
Section: Manipulating Ar Signaling For Prevention and Treatmentmentioning
confidence: 99%
“…Based on the central role of AR in castration resistance, novel AR pathway inhibitors could potentially provide important therapeutics for advanced prostate cancer (Attar et al 2009;Knudsen and Scher 2009). In this regard, a second-generation AR antagonist, MDV3100, which completely lacks agonist activity and binds AR with greater affinity than bicalutamide, has provided new insights into castration resistance, and has given promising results in mouse models and in a human phase 1-2 trial Scher et al 2010).…”
Section: Manipulating Ar Signaling For Prevention and Treatmentmentioning
confidence: 99%
“…Testosterone is the principal androgen in circulation and is synthesized by Leydig cells in the testes, under the regulation of luteinizing hormone (LH), which is further regulated by gonadotropin-releasing hormone (GnRH). Adrenal glands also synthesize a small amount of androgens, such as dehydroepiandrosterone (DHEA) and androstenedione (4-dione) (1). Testosterone enters prostate cells by passive diffusion, where it is converted enzymatically by 5-α reductases to the more potent androgen dihydrotestosterone (DHT) (2).…”
Section: Androgen Signalingmentioning
confidence: 99%
“…On the other hand, ligand-independent activation of AR signaling plays a critical role in initiation and progression of prostate cancer, particularly following androgen ablation therapy (19,20). The role of ligand-independent AR activation in prostate carcinogenesis and progression has been discussed in several excellent reviews (1,21,22). The present review focuses on the effects of androgen signaling during critical phases of prostate carcinogenesis.…”
Section: Androgen and Prostate Carcinogenesismentioning
confidence: 99%
“…However, AR may re-appear and has been shown to be still expressed in the majority of CRPC as well as in a number of androgenindependent prostate cancer cell lines. The AR in the prostate tumor cells draws a great deal of attention from clinicians and researchers, because it mediates not only cell growth and survival but also cell death in response to new hormonal treatments for CRPC cells (Attar et al, 2009a;Chen et al, 2008;Mostaghel et al, 2009;Ross et al, 2008;Vis & Schroder, 2009). Survival and proliferation of CRPC cells have been suggested as mediated by gain-offunction changes in the AR and AR reactivation (Attar et al, 2009a;Chen et al, 2008;Mostaghel et al, 2009;Ross et al, 2008;Vis & Schroder, 2009).…”
Section: Ar In Malignant Prostatic Cellsmentioning
confidence: 99%
“…There are several mechanisms that have been widely suggested that AR still plays an important functioning role in promoting CRPC and can be used as therapeutic target for treating the cancer (Attar et al, 2009a;Chen et al, 2008;Mostaghel et al, 2009;Ross et al, 2008;Vis & Schroder, 2009). These include (1) AR mutations and splicing variations; (2) AR amplification and/or overexpression; (3) de novo androgen production; (4) overexpression of AR co-regulators; and (5) AR activation by non-steroidal growth factors, cytokines, or aberrant AR phosphorylation [please see Attar et al, 2009a;Chen et al, 2008;Mostaghel et al, 2009;Ross et al, 2008;Vis & Schroder, 2009;Steinkamp et al, 2009 for review]. Although we will not further discuss all of these mechanisms, some of them with the recent new findings will be selected for discussion in this article in order to further enlighten the point of views of these mechanisms as well as new derivative concepts of the mechanisms, by which more efficient treatments for CRPC may be developed.…”
Section: Ar In Malignant Prostatic Cellsmentioning
confidence: 99%